Magazines, Intellectual Networks and Areas of Theoretical Incitement (Palimpsesto, 2020)
This article has as a general objective to make a synthesis of the features in common of the editorial projects of Argentine New Left, identifying three different territories or areas of theoretical incitement. Specifically, the idea is to draw structural guidelines in order to facilitate a comparative analysis of those journals. The text applied a long-term perspective for the purposes to systematize the essential characteristics of a diverse, heterogeneous and ephemeral production in terms of duration and circulation, but also visualizes the importance that the network of intellectuals had in those productions.
Keywords: magazines; networks; intellectuals; New Left; Argentina